(untitled) (Indian Journal of Nematology, 2025)
Mungbean (Vigna radiata) is a leguminous crop with considerable significance for its rich nutritional profile. Nevertheless, it faces susceptibility to various diseases and pests, among them the root-knot nematode (Meloidogyne incognita) and the mungbean yellow mosaic virus (MYMV) exert substantial adverse effects on yield and quality. This study endeavours to delve into the impact of biotic stresses induced by the root parasite, M. incognita at inoculum levels of 1 to 4 J2/cc soil, and MYMV infection on the nutritional composition of mungbean seeds. Findings indicate a significant reduction in nutritional components when infested by M. incognita @ 1–4 J2/cc soil, with crude protein decreasing by 20.37 per cent, lipids by 8.44 per cent, carbohydrates by 9.83 per cent, and various minerals such as calcium and iron by over 30 per cent. MYMV infection had a lesser, yet considerable impact, reducing crude protein by 6.93 per cent and other nutrients such as iron by 25.42 per cent and sodium by 6.48 per cent. Combined infections exacerbated nutrient loss, with crude protein dropping by 32.39 per cent and calcium by 35.92 per cent. These findings underscore the importance of integrated pest management strategies in maintaining the nutritional quality of mungbean crops. Nematode control measures of the mungbean not only mitigate losses attributable to nematodes but also partially alleviate crop losses arising from MYMV, thereby retention of nutritional value of seeds.